The effectiveness of a multi-sensory phonological awareness and letter knowledge training programme for disadvantaged first graders - Nadler-Nir, Elizabeth Francis (Division of Communication Sciences and Disorders, 2017)
The study aimed to determine the effectiveness of a multi-sensory phonological awareness and letter knowledge programme for disadvantaged first graders. One control group and one experimental group, each consisting of 20 children, were matched for age, gender, school readiness, socio-economic status and phonological awareness. Twenty-nine sessions of phonological awareness and letter knowledge training were administered to the experimental group while the control group received vocabulary stimulation activities for the same length of time. Results indicated that the programme was highly effective in improving phonological awareness, letter knowledge, reading and spelling skills. The experimental group scored significantly higher than the control group on simple phonological awareness tasks such as segmenting the sounds in a word, letter knowledge and in their ability to read and spell real and pseudowords. The results are discussed in terms of the importance of both phonological awareness and letter knowledge in the process of literacy acquisition.